ANALISIS KUALITAS PRODUK, PELAYANAN, DAN HARGA TERHADAP LOYALITAS KONSUMEN PADA SEBLAK CAK HEN - Fajri, Nurul; Mujiyanti, Sri Ayudha; Sri Darmawati, Lusi Endang (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
The culinary industry in Situbondo Regency continues to grow rapidly, leading to intense competition among local businesses. One of them, Seblak Cak Hen, must maintain its product quality, service performance, and pricing strategy to sustain customer loyalty. This study aims to examine the influence of product quality, service quality, and price on customer loyalty at Seblak Cak Hen. The research applies a quantitative descriptive approach using a survey method with 100 respondents who have purchased the product at least twice. Data were analyzed using multiple linear regression with the assistance of SPSS software. The findings reveal that product quality, service quality, and price all have a positive and significant impact on customer loyalty, both partially and simultaneously. Among these variables, product quality plays the most dominant role in shaping customer loyalty, followed by service and price. The results imply that maintaining consistent flavor, providing responsive and friendly service, and offering reasonable prices aligned with perceived value are key strategies to enhance satisfaction and strengthen customer loyalty.